2011
DOI: 10.1111/j.1365-2702.2010.03553.x
|View full text |Cite
|
Sign up to set email alerts
|

The profile of absconding psychiatric inpatients in Australia

Abstract: Aims and objectives:The purpose of this study was to examine absconding behaviour (a patient leaving the hospital without permission) within acute and rehabilitation wards of one Australian psychiatric institution, in order to describe the characteristics of the absconding patient and these events.Background: Absconding is a significant issue within psychiatric inpatient settings,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
4
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 24 publications
3
39
4
6
Order By: Relevance
“…The relationship between containment and gender or age is often inconsistent between studies (e.g. Knutzen et al, 2014), and the higher proportion of males admitted to acute care inpatient units may account for the present findings (Muir-Cochrane, Mosel, Gerace, Esterman, & Bowers, 2011). Lack of more detailed information about demographics (e.g.…”
Section: Discussioncontrasting
confidence: 46%
“…The relationship between containment and gender or age is often inconsistent between studies (e.g. Knutzen et al, 2014), and the higher proportion of males admitted to acute care inpatient units may account for the present findings (Muir-Cochrane, Mosel, Gerace, Esterman, & Bowers, 2011). Lack of more detailed information about demographics (e.g.…”
Section: Discussioncontrasting
confidence: 46%
“…That said, most studies appear to adopt a broad definition of the behavior, commonly defining absconding as leaving the hospital without permission [16-18] and including a failure to return from an authorized leave [7,8,12,19-21]. In their systematic review of absconding, Bowers and colleagues [1] reported the mean rate of absconding for general psychiatry (excluding forensic services) was 12.6% of all patients ‘at risk’ (defined as the total number of inpatients at the beginning of the study period plus the number of those admitted in the course of the study), with a range of 2-44%.…”
Section: Introductionmentioning
confidence: 99%
“…Risk assessment and management are major components of contemporary mental health practice. Risk, described as "the likelihood of an adverse event happening" (Muir-Cochrane & Wand, 2005, p. 5), can include patient aggression (Daffern & Howells, 2009), suicide and self-harm (Thompson, Powis, & Carradice, 2008), absconding (Muir-Cochrane, Mosel, Gerace, Esterman, & Bowers, 2011), substance abuse (Thomson, 1999), and diverse concerns, such as medical comorbidity, exploitation, social exclusion, victimization, and poverty (Kelly & McKenna, 2004;Muir-Cochrane, 2006). The increasing importance placed on risk assessment and management is reflected in not just policy, but also the daily care of consumers by health care professionals worldwide (de Nesnera, & Folks, 2010;Department of Health, 2007;Langan, 2010;Oordt, Jobes, Fonseca, & Schmidt, 2009).…”
mentioning
confidence: 99%